Pajak Tangguhan dan Tax to Book Ratio dalam Mempengaruhi Kinerja Keuangan: Perusahaan Sektor Pertambangan Indonesia - Saparinda, Raden Wulan; Riyadi, Wulan; Siti Nabilla, Zalfa (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2025)
Financial performance is influenced by several factors, including deferred tax and the tax-to-book ratio. A decline in net profit accompanied by a decrease in revenue occurred in the first semester of 2023 for three coal companies: PT. Adaro Energy Indonesia Tbk, PT. Indo Tambangraya Megah Tbk, and PT. Indika Energy Tbk. The main cause is attributed to the weakness in average selling prices. This study aims to determine whether deferred tax and the tax-to-book ratio have an impact on financial performance (A Study on Mining Companies Listed on the Indonesia Stock Exchange for the Period 2018-2022). The research uses secondary data. The sample consists of mining companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2022, selected using purposive sampling, resulting in 40 data samples. The research method employed includes descriptive and verification statistics. Data is analyzed using SPSS version 25, with tests including classical assumption tests, multiple linear regression tests, coefficient of determination tests, and hypothesis testing. The results indicate that: (1) deferred tax does not have a significant impact on financial performance; (2) the tax-to-book ratio has a significant impact on financial performance; (3) both deferred tax and the tax-to-book ratio have a significant impact on financial performance.